Penyuluhan Untuk Meningkatkan Pemahaman Permasalahan Fiqih wanita Di Kelas 1 Madrasah Tsanawiyah Darussalamah Putri Pondok Pesantren Darussalam Sumbersari - Abdul Aziz; Doni Saputra (LP3M IAIFA Kediri, 2021)
Women should get the highest and highest education, because women are the creators and shapers of a quality future society. Because a woman in Islam reflects the existence of Islam, when Islamic society succeeds then the position of women is so. Therefore, islam elevates the position of women by giving their rights specifically, especially understanding islamic shari'ah.'at. In the study itself the author chose to use the PAR (Participatory Action Research) method. The results of this study, do some of the following steps; The first step we do is to prepare the material that we will deliver. The second step is to need methods and approaches that are flexible according to the circumstances. Because, there is often a gap between plans and practices on the ground. The third step is to evaluate the counseling that has been carried out from start to finish to children. This is in an attempt to find out the extent of the material that has been captured by children while during counseling.